The murder of Piersanti Mattarella and the Sicilian Region Law 51/80. To the origins of anti-mafia education in Italian schools (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
The paper outlines the historical context in which Sicilian Regional Law No. 51/80, which for the first time introduced in-depth programs on the Mafia into the schools, took shape. A recon-struction of the reasons that led to the murder of the president of Sicily, Piersanti Mattarella, in the aftermath of which the law saw the light of day, is followed by a bibliographical note on the history of education of lawfulness in Italian schools.
Keywords: Piersanti Mattarella; mafia; school; education of lawfulness; Sicily